Analisis Kalimat Perundungan dalam Film Die Welle - Ruth Saida Pangaribuan; Tanti Kurnia Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The objective of this study was to identify the forms of bullying sentences in the film